Cross-border DSM as a complement to storage and RES in congestion management markets - Ponoćko, Jelena; Mateska, Aleksandra Krkoleva; Krstevski, Petar (Elsevier BV, 2023)
This paper proposes a regional congestion management (CM) market framework based on the cross-border use of demand-side flexibility resources, focusing on flexible load connected or aggregated at the transmission level, but also considering flexibility of storage and renewable energy sources (RES). It compares the CM potential of national and cross-border resources in an interconnected transmission system in South-East Europe (SEE). The studies observe the role of location, flexible capacity, availability and type of resource, as well as the cost of congestion elimination, on the effectiveness of CM. The cost-effectiveness of CM is critically assessed based on a bid selection algorithm that considers different bidding scenarios, predefined line flow reduction on a critical line, as well as the operating constraints of the transmission network.
Keywords: Demand side management, FlexibilityCongestion management market, Transmission network